Pengaruh Celebrity Endorser Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Produk Pantene Miracles Hair Supplement Conditioner (Studi Kasus Pada Followers Instagram @Panteneid) - Annisa Nurul Mustopa; Novian Ekawaty (Peneliti.net, 2022)
The objectives of this study are: (1) To determine the relationship or correlation between Celebrity Endorser and Electronic Word of Mouth; (2) know the influence of Celebrity Endorsers and Electronic Word of Mouth on Purchase Decisions partially and simultaneously. This study uses quantitative methods with path analysis techniques. The sample in this study used the slovin formula taken from the total study population, namely Instagram followers @Panteneid, which amounted to 400 respondents. The test results in this study used SPSS 22 to show a correlation of 18,119 t > t table of 2,249. The result of partial data processing of the Celebrity Endorser variable (X1) to the Purchase Decision (Y) resulted in a t count of 0.442 < t table of 2,249. The result of partial data processing of the Electronic Word of Mouth (X2) variable against the Purchase Decision (Y) resulted in a t count of 12,095 > t table of 2,249. The result of simultaneous data processing of the Celebrity Endorser (X1) and Electronic Word of Mouth (X2) variables to the Purchase Decision (Y) resulted in a calculated f value of 117,346 > f table of 3,018. The conclusion was that a strong correlation was found in the variables Celebrity Endorser (X1) and Electronic Word of Mouth (X2). The Celebrity Endorser (X1) and Electronic Word of Mouth (X2) variables are stated to have a parsilan and simultaneous effect on the Purchase Decision (Y).